PAPAKINOTO (PENEBAR PAKAN IKAN OTOMATIS) â€˜UPAYA PENINGKATAN PRODUKSI DAN EFIISIENSI WAKTU BUDIDAYA TAMBAK IKAN TAWAR MASYARAKAT BELAWA KABUPATEN SOPPENGâ€ - Wahyuni, Sri; Mudarris, Mudarris; Askar, Ambo; Ayusnin, Siti Reski; Zain, Satria Gunawan (Jurnal Pendidikan Teknologi Pertanian, 2018)
PAPAKINOTO is an additional technology requirement for freshwater pond fishermen. This tool consists or Arduino Atmega 16 microcontroller circuit as a control center in the distribution of fish feed. Using of this tool will set the schedule of fish tool will set the schedule of fish automatically after the pre-arranged center control. From the system test conductedÂ  that fish feed was scheduling system and fish distribution successfully with 100% rate of success. All systems designed by the team are considered successful because the tool runs well